MAPPING IMPACT OF DESIGN THINKING IN TEAMWORK, PROBLEM-SOLVING AND CREATIVITY. (May 2020) - Guaman-Quintanilla, S.; Chiluiza, K.; Everaert, P.; Valcke, M.
Abstract: The present study analyzes the impact of a Design Thinking course on undergraduate students during an academic term. The impact was measured on three key outcomes: teamwork, problem-solving and creativity; using VALUE rubrics. The evaluation was carried out at three different moments during the course. Three types of evaluators participated: facilitators, students (self-evaluation) and peers. The results show statistically significant improvement on the three outcomes comparing students' initial and final performance. Despite the promising results, the current study has some limitations.